Complete Genome Sequence of the Bioleaching Bacterium Leptospirillum Sp. Group Ii Strain Cf-1 - Levican-Jaque, G; Valdes-Parra, N (Elsevier B.V., 2016)
We describe the complete genome sequence of Leptospirillum sp. group II strain CF-1, an acidophilic bioleaching bacterium isolated from an acid mine drainage (AMD). This work provides data to gain insights about adaptive response of Leptospirillum spp. to the extreme conditions of bioleaching environments. © 2016 Elsevier B.V.